Politics on a plate: equivocal communication in Indonesian presidential nutrition policy - Sianturi, Hendry Roris P. (Frontiers in Communication, 2025)
Prabowo Subianto, the President of Indonesia, has recently launched a flagship initiative known as Makan Bergizi Gratis (MBG), like a free school meals program, as part of his political campaign for the 2024 presidential election. This study using sentiment analysis of 4,041 news reports in social media posts collected with Talkwalker analytic tools between 6 and 12 January 2025. In the first week, social media sentiment was predominantly negative, with 41.2% expressing unfavorable views, 13.1% positive sentiments, and 45.7% neutral responses. A key issue in the program’s implementation is equivocal communication, amid the community’s demand for clear information.